Novel hybrid-glass-based material for infiltration of early caries lesions. Issue 6 (June 2022) - Nedeljkovic, Ivana; Abdelaziz, Marwa; Feilzer, Albert J.; Szafert, Slawomir; Gulia, Nurbey; Dawaa, Monostoi; Krejci, Ivo; Kleverlaan, Cornelis J.
Abstract: Objectives: To assess the effectiveness of two experimental, hybrid-glass-based infiltrants in arresting artificial white spot lesions (WSLs) in vitro, and to compare it with resin-based infiltrant Icon. Methods: Artificial WSLs were formed on bovine enamel specimens (n = 68). Specimens were divided into four groups according to WSLs treatment: 1) no-treatment control (NTC), 2) infiltration with Icon (Icon), 3) infiltration with experimental hybrid-glass material (EXP), and 4) infiltration with experimental hybrid-glass material containing hydroxyapatite (HAp) nanoparticles (1%) (EXP-HAp). Half of the specimens from each group were subjected to cariogenic challenge using pH-cycling, consisting of a 7-day alternate incubation (37⁰C) in demineralization (4 h/day, pH=4.6) and remineralization solutions (20 h/day, pH=7.2). Another half of the specimens was incubated in distilled water (control). Caries progression was assessed by measuring surface micro-hardness (SMH), roughness (Ra ) and average surface level, and by analyzing WSLs morphology. Non-cycled and pH-cycled specimens were compared with Man-Whitney U test, while different treatment groups were compared with Kruskal-Wallis test with pairwise comparisons (p < 0.05). Results: In all groups (NTC, Icon and EXP-HAp) except EXP, SMH decreased significantly after pH cycling. In addition, SMH increased in EXP upon pH cycling and was significantly higher than in other pH-cycled groups (<0.001). Ra increased considerably, while surface level decreased after pH cycling in all groups except in EXP. Signs of demineralization and roughness increase in NTC, Icon and EXP-HAp were also observed with the SEM. Significance: Experimental hybrid-glass-based material without HAp-nanoparticles could completely arrest the progression of WSLs, unlike its version with HAp-nanoparticles and resin-based infiltrant Icon. Highlights: Hybrid-glass-based infiltrant can completely arrest early caries lesions The hardness of new hybrid-glass-based material increases in acidic environment. Hybrid-glass-based infiltrant is more biostable than methacrylate-based Icon. Hybrid-glass-based infiltrant is a viable alternative to methacrylate-based Icon.